CHARACTERIZATION OF SEA GRAPES (Caulerpa lentillifera) FROM VIETNAMESE COMPANY’S PRODUCTS - Imran Lapong; Nicholas Paul; Akbar Reza (Hasanuddin University, 2019)
Species of sea grapes (Caulerpa spp.) are consumed broadly in many regions such as in Southeast Asia and Pacific areas. However, it damages easily if packed incorrectly and may only last for couple of days. A company in Vietnam (Tritin Pty Ltd) has developed a preservation technique for sea grapes that enables export to many countries. The aim of this study is to characterization of the Vietnamese company’s product of Caulerpa. The study found that the product based on a 10% brine concentration (114.33 g/L ±2.30 SD). The average weight of each sachet package is 22.47 g ±0.37 containing 65 fronds of Caulerpa lentillifera. The average weight and length of the fronds is 0.73 g ±2.30 SD and 7.27 cm ±1.59 SD. There was a significant relationship between the weight and the length of the fronds during the rehydration process in freshwater (R2=0.35, p<0.01), with rehydration of weight and length complete after x seconds